Forensic determination of crossing lines involving stamp and pen inks by mass spectrometry imaging. Issue 7 (4th February 2020) - Rodrigues de Morais, Damila; Campêlo, Jacqueline de Morais; Razzo, Daniel; Eberlin, Marcos Nogueira; Costa, José Luiz; Santos, Jandyson Machado
Abstract : The mass spectrometry imaging (MSI) and easy ambient sonic-spray ionization (EASI) were used to identify the sequence of lines in intersecting points between stamp and pen inks, which can solve one of the most challenge task for the forensic cases. Abstract : One of the most challenging tasks in forensic cases is to identify the intersection sequence of lines and inks in questionable documents, mainly in those involving significant financial values such as insurance claims, wills and contracts. Optical examination using microscopy images has been commonly used, but this morphological examination presents severe limitations that can lead to false conclusions. Herein, we show that mass spectrometry imaging (MSI) using easy ambient sonic-spray ionization (EASI) can be used to accurately identify the sequence of lines at intersecting points between stamp and pen inks. First, we used proof of concept cases and ion images, and extracted ion chronograms and EASI-MS profiles to evaluate how they could identify the intersection sequences. EASI-MSI was then used to distinguish the sequence of intersecting lines in two cases of simulated contract documents in which a signature made from pen ink was placed under or above the stamp ink. We demonstrate that EASI-MSI provided a clear indication of the actual sequence, showing that it functions as an efficient and rather unequivocal analytical tool in the examination of crossing ink lines when stamping is involved.